2017
DOI: 10.1002/pssr.201700010
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature ferromagnetic‐like response in “bulk” Y‐doped CeO2

Abstract: Strong ferromagnetic-like response is observed at room temperature in "bulk"and nano-crystalline Y-doped CeO 2 . The saturation magnetization for "bulk" ($600 nm) crystallites of CeO 2 doped with 25 at.% Y is more than an order of magnitude higher compared to its nanocrystalline ($10 nm) counterpart. High frequency electron spin resonance and 89 Y nuclear magnetic resonance measurements indicate clustering of electronic defects in the "bulk" crystallites. The remarkable size dependence of the magnetic behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“… (for x = 2; 4; 6; 8; 10% − JdY = 33; 35; 40; 46; 55 meV, respectively). This leads to increasing of the magnetization M (see Figure ) what is in qualitative agreement with the experimental data of Rakhmatullin et al Lee et al reported also an increase of the magnetization M with increasing of Ce 3+ ions. But Lee et al showed that as the content of Y 3+ is enhanced, the concentration of Ce 3+ increases for 0x5% and then begins to decrease for normalY3+>5%.…”
Section: Numerical Results and Discussionsupporting
confidence: 90%
“… (for x = 2; 4; 6; 8; 10% − JdY = 33; 35; 40; 46; 55 meV, respectively). This leads to increasing of the magnetization M (see Figure ) what is in qualitative agreement with the experimental data of Rakhmatullin et al Lee et al reported also an increase of the magnetization M with increasing of Ce 3+ ions. But Lee et al showed that as the content of Y 3+ is enhanced, the concentration of Ce 3+ increases for 0x5% and then begins to decrease for normalY3+>5%.…”
Section: Numerical Results and Discussionsupporting
confidence: 90%
“…Doping ceria with aliovalent cations such as rare earth or transition metal ions generates more vacancies and in a number of cases leads to better performance parameters as well as to the enhancement of room temperature ferromagnetism . A considerably lower number of publications are devoted to the studies of anion doping effects to ceria.…”
Section: Sample Notations Average Particle Sizes Treatment Temperatmentioning
confidence: 99%